Association of serum CCL20 levels with pulmonary vascular involvement and primary biliary cholangitis in patients with systemic sclerosis. (22nd March 2021) - Ikawa, Tetsuya; Miyagawa, Takuya; Fukui, Yuki; Minatsuki, Shun; Maki, Hisataka; Inaba, Toshiro; Hatano, Masaru; Toyama, Satoshi; Omatsu, Jun; Awaji, Kentaro; Norimatsu, Yuta; Watanabe, Yusuke; et al.
Abstract: Aim: Systemic sclerosis (SSc) is a chronic autoimmune disease resulting in vasculopathy and fibrosis of the skin and major internal organs. Especially, interstitial lung disease and pulmonary arterial hypertension are the leading causes of mortality. C‐C motif ligand 20 (CCL20) is known as a homeostatic and inflammatory chemokine, which is associated with fibrosis and angiogenesis and constantly expressed in organs involved in SSc. Therefore, we investigated the potential contribution of CCL20 to the development of SSc. Method: We conducted cross‐sectional analyses of 67 SSc patients and 20 healthy controls recruited in a single center for 9 years. Serum CCL20 levels were measured by enzyme‐linked immunosorbent assay. Statistical analyses were performed with the Mann‐Whitney U test, the Kruskal‐Wallis test followed by Dunn's multiple comparison test, Fisher's exact probability test and the Spearman's rank correlation coefficient. Results: SSc patients had significantly higher serum CCL20 levels than healthy controls. In SSc patients, serum CCL20 levels correlated inversely with the percentage of predicated diffusion lung capacity for carbon monoxide and positively with mean pulmonary artery pressure (mPAP). In addition, SSc patients with increased serum CCL20 levels had anti‐mitochondrial antibody M2 titer significantly elevated relative to those with normal levels, and SSc patients with asymptomatic primary biliary cholangitis (PBC) possessed higher serum CCL20 levels than those without. Importantly, serum CCL20 levels were associated positively with mPAP values and PBC presence by multivariate regression analysis. Conclusion: Serum CCL20 levels may be involved in the development of pulmonary vascular involvement leading to pulmonary arterial hypertension and asymptomatic PBC in SSc patients.